Educational Processes in the Creation of Youth Fitness Dance Among the Northern Sichuan Qiang Ethnic Group in Chengdu - Guo, Zhenni; Moonsuwan, Thanyalak (Journal of Posthumanism, 2025)
This study investigates the educational processes involved in developing a culturally integrated youth fitness dance inspired by the traditional motions of the Northern Sichuan Qiang ethnic group. The initiative, based on exercise physiology, human anatomy, and ethnographic study, aims to combine the expressive features of Qiang dance with the regimented style of modern aerobics. To assure cultural authenticity and pedagogical appropriateness, the creative team undertook extensive fieldwork in Qiang communities, spoke with local folk artists, and worked with educational institutions. It comprises four primary movement phases totaling 288 beats and incorporates symbolic dance components such as axial rotation, hip circling, and the characteristic Guozhuang style. Traditional Qiang instruments and melodies were combined with contemporary beats to increase involvement and authenticity and costume design to show cultural identity while ensuring utilitarian performance. Pilot initiatives in Chengdu schools resulted in high student involvement, favorable feedback, and greater cultural understanding. This initiative provides a unique model for physical education and helps preserve and revitalize Qiang’s intangible cultural legacy via creative educational practice.